Organizational Culture Towards Culture of Excellence - San Jose, Manolito (Jurnal Politikom Indonesiana, 2022)
This study examined the organizational culture of the College of Education of Polytechnic University of the Philippines. An institution’s organizational culture determines the faculty members’ attitudes, values, characters, goals, and aspirations. It identifies their nature and how they act or perform their duties and responsibilities no matter what their position is. Adopting a positive culture in an institution produced a positive outcome, promoting success in the organization. Loyalty to the organization is one of the greatest assets of the faculty members working in the College. Unity amidst the diversity exists in the College of Education that makes the organization continue to succeed and strive for excellence. According to Edgar Schein (1985), "organizations do not adopt a culture in a single day. Instead, it is formed in due course of time as the employees go through various changes, adapt to the external environment, and solve problems. The researcher used Qualitative Descriptive Design as a comprehensive summarization of specific events and phenomena experienced by individuals or groups of individuals using interview methods both online and offline platforms. Keywords: Organizational Culture, Beliefs, Values, Character, Service, Loyalty, and Excellence.